UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN FISIKA MELALUI METODE FISHBOWL PADA SISWA KELAS XII IPA.1 SMAN 1 TALAMAU - Syainona Refni (STKIP Pesisir Selatan, 2017)
ABSTRACT Based on the results of student learning Class XII IPA.1 SMAN 1 Talamau in subjects Sub physics Applying the concept and principles of wave symptoms in solving the problem found that the results of student learning in physics is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about Improvement Efforts of student learning outcomes in sub physics subjects Applying the concept and principles of wave symptoms in solving problems through Fishbowl Method in Class XII IPA.1 SMAN 1 Talamau Kabupaten Pasaman Barat. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 23 students of Class XII IPA.1 SMAN 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the Fishbowl method can improve student learning outcomes in sub physics subjects Apply the concept and principles of wave symptoms in solving problems in SMAN 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 55.13 (Enough) increased to 84.22 (good) with an increase of 29.09%.Keywords: Learning Outcomes, Physics, Fishbowl Method